Sistema de detecção de objeto personalizado utilizando inteligência artificial - Marques, Lucas de Souza (2020)
This work aims to develop an automatic object verification system on a production line. Currently, there is a market for object detection that comprises values above R$ 100 thousand reais for the implementation of the same project. The project is based on being developed on a completely Open Source platform. The proposal consists of creating a low-cost Python language system that solves the problems of instantaneous line stops and field problems related to the lack of the object and make it portable to any computer. Due to the fast time of the line some boxes go unnoticed in the eyes of the operator and with the implemented system it is expected that all boxes are controlled and detect all manuals and take their own actions autonomously without the need for human intervention following the concept of industry 4.0. The developed system had quick responses (about 40 milliseconds) for the evaluation of each image and is already implemented in the factory.